MISE EN SCÈNE DES NORMES DE GENRE SUR LES AFFICHES ET PHOTOS PROMOTIONNELLES DES SÉRIES ET FILMS DE SUPERHÉROÏNES - Dr. Sébastien HAISSAT ,Dra. Anne PARIZOT (Fonseca, Journal of Communication, 2023)
This article aims to study and define gender norms in the specific space of movie and television series posters and promotional photos. The comparative analysis will focus on two superheroines, Wonder Woman and Catwoman, two contrasting but representative figures of two identifiable faces as solar versus lunar, implicitly narrated but visually explicit. The contextualization of the appearance of these superheroines and the diachronic approach chosen thus reveal the evolution of these norms.